Seed Potato Production Business through a Gender Lens - Mwesige, Rose; Etiang, Joseph; Kyarisiima, Sarah; Aheisibwe, Ambrose; Kwikiriza, Gerald; Muhereze, Ronald; Ayahura Kutesa, Ronald; Barekye, Alex; Constraints, Gender; Seed-potato, Opportunities; Participation, Production (Gender and Women’s Studies, 2019)
Potato (Solanumtuberosum) is an important crop in highland areas of South Western and Eastern Uganda. Seed potato business is a key input for increasing potato productivity and contributes to people livelihood. Attempts to increase seed potato production and its contribution to livelihoods of men and women have not addressed a gap in seed demand and on its contributions to incomes of the farming households. Seed producers and research provides 0.15 % of the total seed potato required. This has partly been attributed to lack of involvement of men and women in seed potato production business, leading to low yields averaging 7.5 t/ha. This research aimed at finding out factors affecting involvement of men and women in seed potato business. Questionnaires, focus group and individual interviews of key informants were conducted involving men and women selected from 3 different locations. Results indicated that men are more involved in seed potato production, own more capital resources, and are mostly head household giving them an upper hand in decision making. Most men tended to engage in key activities leading to preparation for marketing. This gives them an opportunity to negotiated for market prices, sell and receive cash on behalf of their wives. Women tended to concentrate in domestic responsibilities such as feed the family. Women refrained from engaging in key activities in the seed potato business, which undermines the benefits that accrue to them.
Keywords: Gender; Constraints; Opportunities; Seed-potato; Production; Participation